Analysis of Success Factors of Gojek Startup Services Compared to Other Competitor Startup Services - Laksmana , I Nyoman Hendra; Ningsih, Riska Apriliati (TECHNOVATE: Journal of Information Technology and Strategic Innovation Management, 2024)
In the past few years, many startups starting to establish. This is because of the development of Information Technology which spurs the development of human life in today's digital era. However, does all established startups can survive and generate profits as expected by the company? Of the many failures experienced by startups, there are 2 factors that cause it, such as internal and external factors of the company. The company's internal factors that commonly occur include; less solid team, inaccurate business model, etc. While the company's external factors are the level of competition that is too high, inaccurate in targeting the target market, inaccurate marketing strategies, and many more. One of the startups that can survive and generate substantial profits in Indonesia is Gojek. Behind its success, there are several factors that support Gojek so that it can survive to this day compared to other competing startups. This study uses 2 research methods; Questionnaire and observation. The purpose of this research journal is expected to find out what factors are the success of Gojek. The results of research through questionnaires show that the many services, quality and information offered by Gojek have also become the reason users use this application compared to other competing startups.